The Flesh of Stories of Pain and Suffering - István Fazakas (Études Ricoeuriennes / Ricoeur Studies)
The paper explores the difference between semiology and hermeneutics of pain and suffering by focusing on narrativity and the body. First, it recapitulates some historical distinctions between explaining and understanding in the context of psychopathology. It shows how the hermeneutic method culminates in the idea of the cohesion of life, constituted through biography and narrative. The second section deals with the relationship between narrativity and selfhood in stories of suffering. The third part addresses the problem of the lived body and the ante-predicative embodiment of suffering and pain, which fuse with the ambiance, coloring the lifeworld.